Internalization of Islamic Educational Values in the Cecah Inai Tradition of the Natuna Malay Community - Yurnalis Yurnalis; Abdul Haris; Syamsurizal Yazid (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aimed to describe the process of internalizing Islamic educational values in the Cecah Inai tradition among the Malay community in Bunguran Timur District, Natuna Regency. The research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, involving traditional leaders, Mak Inang (female ceremonial leaders), and local cultural officers. The findings showed that the Cecah Inai tradition was not merely a cultural ceremony within the Malay wedding sequence but also functioned as a medium for imparting Islamic values that became internalized in the community’s social life. The values that emerged in this tradition included aqidah values (faith and monotheism toward Allah), shari’ah values (obedience to laws and social etiquette), and akhlaq values (courtesy, patience, and moral responsibility). The Cecah Inai procession demonstrated a harmonious integration between customary practices and Islamic teachings, which characterized the culture of the Natuna Malay community. This study affirmed that local traditions played an important role as a non-formal educational medium in shaping character and strengthening the community’s Islamic identity.